2002
DOI: 10.1029/2001wr000494
|View full text |Cite
|
Sign up to set email alerts
|

Preferential flow and pesticide transport in a clay‐rich till: Field, laboratory, and modeling analysis

Abstract: 1] This study investigates vertical flow and pesticide transport along fractures in water saturated unoxidized clayey till. From two experimental fields, each 40 m 2 , 96% and 98%, respectively, of total vertical flow was conducted along fractures in the till, while the remaining 2-4% of flow occurred in the clay matrix at very slow flow rate. An applied dye tracer was observed only along 10-26% of the total fracture length measured on the horizontal surface of the experimental fields. In vertical sections the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 24 publications
8
68
0
Order By: Relevance
“…The root volume of the horizons investigated in this study accounted for 0.05 to 6.5% (median 0.78%) of the total soil volume. Assuming that water flowed along roots and root channels, as Jørgensen et al (2002) claim, the root volumes we found are comparable to the macropore volume as described by Alaoui and Helbling (2006).…”
Section: Discussionsupporting
confidence: 75%
“…The root volume of the horizons investigated in this study accounted for 0.05 to 6.5% (median 0.78%) of the total soil volume. Assuming that water flowed along roots and root channels, as Jørgensen et al (2002) claim, the root volumes we found are comparable to the macropore volume as described by Alaoui and Helbling (2006).…”
Section: Discussionsupporting
confidence: 75%
“…Both decayed and live roots can provide avenues for macropores associated with root channels (Devitt and Smith, 2002). It was found that more than 90% of water in clay-enriched soils flowed through root channels, while less than 10% flowed along fractures without root channels (Jørgensen et al, 2002). In our study, soil hydraulic conductivity closely correlated to root mass density (P<0.05).…”
Section: Factors Impacting the Soil Infiltration Processsupporting
confidence: 60%
“…Rapid movement of metsulfuron-methyl in soil, as we found to occur at the Cumberland Plateau study site, has been reported for several soils and in glacial till subsoil (Heistermann et al, 2003;Jorgensen et al, 2002;Ismail and Tet-Vun, 2003). The organic carbon and other components of the soil at our study site exhibited very low affinity in retaining the herbicides.…”
Section: Discussionsupporting
confidence: 69%